PENGARUH WORK-FAMILY CONFLICT TERHADAP KEPUASAN KERJA DAN KINERJA (Studi pada perawat wanita RSUD Wonosari Yogyakarta) - Anandyas Khoirunnisa Retnaningrum; Mochammad Al Musadieq (Jurnal Administrasi Bisnis, 2016)
The aim of this research is to analyze the impact of work family conflict on nurse’s job satisfaction and nurse’s performance. The variables of this research are work interference with family, family interference with work, nurse’s job satisfaction, and performance of nurse’s. This is an explanatory research with quantitative approach. The scope of this research is identified as all the women nurses of RSUD Wonosari Yogyakarta, with the number of sample are 51 nurses. That sample is obtained by using Slovin formula. Data is collected directly from respondents using a questionnaire research instruments. Data analysis include descriptive analysis and path analysis which were processed using SPSS v 22.00. The research shows that work interference with family has negative and significant influence toward nurse’s job satisfaction and nurse’s performance, family interfence with work has negative and significant influence toward nurse’s job satisfaction and nurse’s performance, nurse’s job satisfaction significantly influence toward nurse’s performance. The direct effect of work interference with family toward nurse’s performance is greater than indirect effect through nurse’s job satisfaction and nurse’s job satisfaction was not mediated the relation between work interence with family toward nurse’s performance, so do the family interence with work toward nurse’s performance. Keywords : Work intereference with family, Family interference with work, Nurse’s Job Satisfaction, Nurse’s Performance ABSTRAK Penelitian ini bertujuan mengetahui pengaruh work family conflict terhadap kepuasan kerja dan kinerja. Variabel penelitian ini meliputi work interference with family, family interference with work, kepuasan kerja perawat, dan kinerja perawat. Penelitian ini merupakan penelitian penjelasan dengan pendekatan kuantitatif. Penelitian ini menjangkau perawat wanita RSUD Wonosari Yogyakarta dengan jumlah sampel 51 perawat. Sampel tersebut diperoleh menggunakan rumus Slovin. Data diperoleh langsung dari responden dengan menggunakan angket. Analisis data meliputi analisis deskriptif dan analisis jalur yang diolah menggunakan SPSS versi 22.00. Penelitian ini menunjukkan work intereference with family berpengaruh negatif signifikan terhadap kepuasan kerja perawat dan kinerja perawat, family intereference with work berpengaruh negatif signifikan terhadap kepuasan kerja perawat dan kinerja perawat, serta kepuasan kerja perawat berpengaruh signifikan terhadap kinerja perawat. Pengaruh langsung work interference with family terhadap kinerja perawat lebih besar daripada pengaruh tidak langsung melalui kepuasan kerja perawat serta kepuasan kerja perawat tidak memediasi hubungan antara work interference with family terhadap kinerja perawat, begitu juga family intereference with work terhadap kinerja perawat. Kata Kunci : Work intereference with family, Family interference with work, Kepuasan Kerja Perawat, Kinerja Perawat